209k views
2 votes
3(2x−7)+ 1/ 3 (7x+2)

User Ryche
by
4.9k points

2 Answers

1 vote

Explanation:

Hey there!

Given;

= 3(2x-7) + 1/3(7x+2)

Let's simplify them.


= 3(2x - 7) + (1)/(3) (7x + 2)


= 6x - 21 + (7x + 2)/(3)


= (3(6x - 21) + 7x + 2)/(3)


= (18x - 63 + 7x + 2)/(3)


= (25x - 61)/(3)

Therefore the answer is (25x-61)/3.

Hope it helps...

User The Real Bill
by
5.3k points
3 votes

Answer:


\quad (25x+2)/(3)-21

Explanation:


3(2x-7)+ 1/ 3 (7x+2)\\\\\mathrm{Expand}\:3\left(2x-7\right):\quad 6x-21\\=6x-21+(1)/(3)\left(7x+2\right)\\\\\mathrm{Expand}\:(1)/(3)\left(7x+2\right):\quad 7*(1)/(3)x+2* (1)/(3)\\\\=6x-21+7*(1)/(3)x+2*(1)/(3)\\\\\mathrm{Simplify}\:6x-21+7*(1)/(3)x+2*(1)/(3):\\\\\quad (25x+2)/(3)-21

User MurugananthamS
by
4.8k points